Comparison of Numbered Head Together and Teams Games Tournament Cooperative Models on the Learning Outcomes in Mathematics Learning - Anggraini, Yulia Sari; Neviyarni; Ahmad , Syafri (International Journal of Elementary Education, 2024)
This study is a comparative experimental study that aims to obtain information on whether there are differences in learning outcomes between students taught using the Numbered Head Together (NHT) cooperative learning model and students taught using the Teams Games Tournament (TGT) cooperative learning model. The population of the study was two classes IV of elementary school. The sampling technique used was random sampling to determine experimental class I and experimental class II, each class consisting of 23 and 22 students. Data were collected through objective learning outcome tests in both experimental groups. The data in this study were analyzed using descriptive statistical analysis techniques and inferential statistics. The results of the descriptive analysis showed that the learning outcomes of grade IV students who were taught using the NHT-type cooperative learning model had an average value of 81.04 with a standard deviation of 9.2022.In contrast, the learning outcomes of students taught using the TGT-type cooperative learning model had an average value of 85.09 with a standard deviation of 9.2526. Inferential analysis was carried out using the Independent Samples t-test to compare the average learning outcomes of the two groups, with testing the assumption of homogeneity of variance through Levene's Test. The results of the inferential analysis showed that there was no significant difference between the mathematics learning outcomes of students taught using the NHT-type cooperative learning model and the mathematics learning outcomes of students taught using the TGT-type cooperative learning model.